2005
DOI: 10.1371/journal.pgen.0010070
|View full text |Cite
|
Sign up to set email alerts
|

Clines, Clusters, and the Effect of Study Design on the Inference of Human Population Structure

Abstract: Previously, we observed that without using prior information about individual sampling locations, a clustering algorithm applied to multilocus genotypes from worldwide human populations produced genetic clusters largely coincident with major geographic regions. It has been argued, however, that the degree of clustering is diminished by use of samples with greater uniformity in geographic distribution, and that the clusters we identified were a consequence of uneven sampling along genetic clines. Expanding our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

42
583
5
6

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 518 publications
(636 citation statements)
references
References 21 publications
42
583
5
6
Order By: Relevance
“…Conversely, in this study we were able to identify two clusters and assign individuals almost consistently to their geographic origin, despite F st being only 0.8%, probably due to the fact that Latch and colleagues considered lower numbers of markers and individuals. 9,45 We corroborated our result showing that: (a) individuals belonging to clusters are also genealogically related to other cluster members (by correlating membership coefficients inferred from genomic analysis and average kinship with other cluster members; Figure 2); and (b) the higher the average membership coefficient for a cluster, the greater the kinship between cluster members (as shown by the significant increase in average kinship with increasing membership stringency; Supplementary Table 1).…”
Section: Discussionsupporting
confidence: 85%
“…Conversely, in this study we were able to identify two clusters and assign individuals almost consistently to their geographic origin, despite F st being only 0.8%, probably due to the fact that Latch and colleagues considered lower numbers of markers and individuals. 9,45 We corroborated our result showing that: (a) individuals belonging to clusters are also genealogically related to other cluster members (by correlating membership coefficients inferred from genomic analysis and average kinship with other cluster members; Figure 2); and (b) the higher the average membership coefficient for a cluster, the greater the kinship between cluster members (as shown by the significant increase in average kinship with increasing membership stringency; Supplementary Table 1).…”
Section: Discussionsupporting
confidence: 85%
“…A general conclusion from these studies was that human genetic variation is greatly influenced by geography, with genetic differentiation between populations increasing with geographic distance and genetic diversity decreasing with distance from Africa (Relethford, 2004;Prugnolle et al, 2005;Ramachandran et al, 2005;Liu et al, 2006). There has also been some debate over the relative importance of the discontinuities in this pattern of isolation by distance (Kittles and Weiss, 2003;Serre and Pääbo, 2004;Manica et al, 2005;Rosenberg et al, 2005;Witherspoon et al, 2006;Handley et al, 2007;Linz et al, 2007). Recent developments in marker discovery will undoubtedly allow this picture to be refined and lead to a muchimproved understanding of human population structure and past settlement history.…”
Section: Introductionmentioning
confidence: 99%
“…where the influence of five variables was evaluated on the clustering of individuals using markers such as the loci number, sample size, group number, geographical dispersion of the sample and assumptions about the correlation of the studied allelic frequencies, Rosenberg et al (2005) observed that each of these variables had an effect on the clustering. When the geographical dispersion was used as a variable and the other variables as constants, the geographical dispersion had a very small effect on the clustering capacity (Helmer et al 2003).…”
Section: Resultsmentioning
confidence: 99%